The role of chief executive officer - Glick, Margaret B., author; Chermack, Thomas J., advisor; Gloeckner, Gene W., committee member; Lynham, Susan A., committee member; Bond, Jennifer K., committee member (Colorado State University. Libraries, 2011)
The purpose of this study was to address the gap between what is reported in the literature and what is known in current practice on the role of CEO. Research on the role of CEO is conflicting and outdated, and the theory deduced by Mintzberg in the 1970s has not been continually refined and updated, a necessary process for maintaining the usefulness of a theory (Lynham, 2002). A major goal of this research was to use the insights provided by CEOs to improve our general understanding of the major roles played by CEOs and how they generally allocate their time in various critical functions. CEOs are known for being a difficult population to research, yet this study has shown they are not inaccessible. This research was also intended to serve those responsible for identifying CEO candidates, recruiting CEOs, coaching CEOs, sustaining an organization's leadership system, and developing performance matrices for Boards of Directors who are ultimately responsible for making sure the CEO is effective and efficient. To investigate the role of CEO a survey instrument was developed based on 31 roles identified in the literature. The survey was sent to CEOs selected from a purchased database by e-mail. The study focused on three research questions with the purpose of understanding the role of CEO, how CEOs allocate their time to roles, and what new roles are identified by CEOs. Eight research hypotheses were tested to understand the impact of gender, company ownership status, age, years in current job, years as CEO, and company size, on the roles agreed with and time allocations. There were a number of statistically significant findings with small effect sizes. The most significant differences were among company sizes, defined by number of employees. Because the survey instrument was developed specifically for this study it does not have a consistent or lengthy track record of valid and reliable survey scores, however, results from a factor analysis reveal high initial scores and a good basis for further instrument refinement and development. This study had implications for CEO role theory. The results provide evidence for adjusting Mintzberg's prior theorizing about the role of CEO, and in this study, many of the roles Mintzberg found were strongly supported, yet some were not. The roles of other researchers and new roles suggested by study participants add depth to Mintzberg's work and serve to update his theory for modern times. The impact of industry on the role of CEO may provide help to CEOs who change industries during their careers. Finally, this study provides implications for practice by providing benchmark data for working CEOs about what their role is and how other CEOs allocate their time to these roles.
Keywords: CEO; role of CEO; chief executive officer